Five new species of the genera Heerz Marsh, Lissopsius Marsh and Ondigus Braet, Barbalho and van Achterberg (Braconidae, Doryctinae) from the Chamela-Cuixmala biosphere reserve in Jalisco, Mexico - Zaldivar Riverón, Alejandro (2012)
Five new species belonging to the poorly known Neotropical doryctine parasitoid wasps genera Heerz Marsh (H. ecmahla sp. n. and H. macrophthalma sp. n.), Lissopsius Marsh (L. pacificus sp. n. and L. jalisciensis sp. n.) and Ondigus Braet, Barbalho & van Achterberg (O. cuixmalensis sp. n.) are described from the Chamela-Cuixmala Biosphere reserve in Jalisco, Mexico. Keys to the described species of the above three genera are provided. The phylogenetic placement of the examined taxa is investigated based on mitochondrial (COI) and nuclear (28S, 2nd and 3rd domain regions) DNA sequence data.